Congratulatory Messages Strategy in Facebook and Twitter - Irahim, Nur Hamimah Muhammad; Bakar, Norsofiah Abu (European Publisher, 2019)
The language behaviour study on congratulatory messages in Malaysia’s social media is limited. The language behaviour focuses on face-to-face congratulatory greetings or language behaviour in texts. The language data usage from social media such as Facebook and Twitter is significant in linguistic study. This is because language usage in Facebook portrays the actual language usage among the language speakers. Data from Facebook and Twitter are also authentic data and can be considered as language corpus. With that, this study examines the strategies used by Malay speakers while giving congratulatory messages in Facebook and Twitter. The objective of this study is to analyse the strategies used by the Malay speakers while giving congratulatory messages in Facebook and Twitter. The strategies observed include verbal and non-verbal symbols. This study uses ethnographic approach as the methodology. The data is collected through observation of comments and the usage of non-verbal symbols. The content analysis method is used to analyse the congratulating strategy used by the Malay speakers. The findings show that the congratulatory messages that often used by the Malay speakers are verbal phrases, which are ‘tahniah’ (congratulations) and ‘syabas’ (well done). These phrases are used as illocutionary device in congratulatory messages in Facebook and Twitter. Expressions of gratitude such as ‘Alhamdulillah’ and ‘Terima kasih’ (thank you) are also been used. The observation also shows that expression of praise can also be used as one of the strategies in delivering congratulatory messages.